Regression of experimental endometriotic implants in a rat model with the angiotensin II receptor blocker losartan. Issue 4 (10th October 2014) - Cakmak, Bulent; Cavusoglu, Turker; Ates, Utku; Meral, Ayfer; Nacar, Mehmet Can; Erbaş, Oytun
Abstract Aim Endometriosis is a common disease in women of reproductive age, and many different treatments have been developed, although none has provided a cure. In this study, the efficacy of losartan, an angiotensin II type 1 receptor blocker and an antiangiogenic and anti‐inflammatory agent, on regression of experimental endometriotic implants in a rat model was investigated. Methods Peritoneal endometriosis was surgically induced in 16 mature female Sprague–Dawley rats. The peritoneal endometriotic implant was confirmed after 28 days, and the animals were divided randomly into two groups. The control group (n = 8) was given 4 mL/day tap water by oral gavage, and the losartan group (n = 8) was given 20 mg/kg per day losartan p.o. We compared endometriotic implant size, extent and severity of adhesion, as well as plasma and peritoneal lavage fluid cytokine levels including vascular endothelial growth factor (VEGF) and tumor necrosis factor (TNF)‐α, plasma inflammatory factor pentraxin‐3 (PTX‐3) and C‐reactive protein (CRP) between the treatment groups. Results Mean surface endometriotic area, histological score of implants, adhesion formation, plasma VEGF, TNF, PTX‐3 and CRP levels were significantly lower in the losartan group compared with control (P < 0.05). Furthermore, the peritoneal VEGF level was lower in the losartan group than in the control group (P < 0.001), but peritoneal TNF‐α was similar in both groups (P > 0.05). Conclusion Losartan suppressed the implant surface area of experimental endometriosis in rats and reduced the levels of plasma VEGF, TNF‐α, PTX‐3 and CRP.